What is Behind Yinshun’s Re-statement of the Nature of the Mulamadhyamakakarika? Debates on the Creation of a New Mahayana in Twentieth-century China - Travagnin, Stefania (Buddhist Studies Review, 2013)
Yinshun (1906–2005) is regarded as one of the most eminent monks in twentieth-century Chinese Buddhism. Previous research has argued that Yinshun especially undertook the mission of writing new commentaries on Madhyamaka texts. His efforts provoked a revival of interest towards the Madhyamaka school among contemporary Chinese Buddhists, and a re-assessment of the position of the writings of Nagarjuna within the history of Chinese Buddhism. This article focuses on Yinshun’s restatement of the nature of the Mulamadhyamakakarika, a text that has always been regarded as fundamental in the Madhyamaka/San-lun tradition in China. The first part analyzes Yinshun’s textual study of the Mulamadhyamakakarika, examining his approach to the text, and how he came to terms with previous Chinese traditional textual scholarship and canonical scriptures. The second part discusses Yinshun’s interpretation of the text by moving away from the micro-context of Chinese San-lun scholarship, and addressing the macro-context of the modern Chinese understanding of the Mahayana.